Relation between solubility and surface hydrophobicity as an indicator of modifications during preparation processes of commercial and laboratory prepared soy protein isolates - Wagner, Jorge Ricardo (2000)
Because water solubility is the main hydration property of proteins, solubility values of commercial and laboratory soy protein isolates, prepared under different conditions, were comparatively analyzed. In contrast, the surface hydrophobicity manifested by proteins is a physicochemical property that determines, to a great extent, the tendency of protein molecules to aggregate and so to lose solubility. On these grounds, the solubility of isolates was analyzed as a function of the surface hydrophobicity of their proteins, and, as a result, three well-defined groups of laboratory isolates were identified: (A) native, (B) partially or totally denatured with high solubility and surface hydrophobicity, and (C) totally denatured with low solubility and surface hydrophobicity. Commercial isolates could not be included in any of these groups; they were grouped as (A') partially native and (C') totally denatured. Solubility values in these two groups were similar to those of group C, but the surface hydrophobicity levels were much lower. The different processes leading to the groups mentioned above are discussed, along with the way the soy proteins are influenced by the specific preparation conditions, namely, protein concentration, chemical or thermal treatments, presence of salts, drying, and phospholipid addition, among others.